DEGREES OF COMPARISON OF ADJECTIVES AS AN OBJECT OF LINGUISTIC RESEARCH. FORMS OF DEGREES OF COMPARISON OF ADJECTIVES. NON-STANDARD FORMS OF DEGREES OF COMPARISON IN RUSSIAN - Associate Professor Davlyatova G. N.; Applicant Rakhimova Kh. N. (Western European Studies, 2024)
This article examines the degrees of comparison of adjectives in the Russian language, focusing on their forms and the implications for linguistic research. The analysis delves into the standard categories of comparison—positive, comparative, and superlative— while also addressing the structural and functional aspects that characterize these forms. Additionally, the study highlights non-standard forms of degree comparison, exploring colloquial variations, regional dialects, and innovative usages that reflect evolving linguistic practices within Russian-speaking communities. By investigating these dimensions, the paper aims to provide a comprehensive understanding of how degrees of comparison contribute to meaning-making and communication in Russian, as well as the broader cognitive and sociolinguistic factors at play
Keywords: Degrees of comparison; adjectives; linguistic research